The effect of color attributes on affective experiences in selected consumer products. - Seva, Rosemary
Product developers are turning to new ways of capturing customers. In recent years, researchers have emphasized the importrance of considering emotion in product design. The aim of this project was to investigate the effects of the independent variables: color hue, saturation and brightness of consumer products on emotions and validate the results of previous studies done on the effect of color on emotional responses. Two consumer products that may indicate the customer's personalities were selected (cars and t-shirts) and emotional reactions to independent variables were investigated using eight emotions selected from Russell's circumplex model of Affect. Different color stimuli were presented using a laptop computer. The resulting emotional response demonstrated high correlation for both cars and t-shirts, but the significance of color attributes was only observed in cars. Emotional responses due to brightness had high consistency and dominated other color attributes in causing emotions. Higher brihtness cause positive emotions to be experienced more intensely while lower brightness produce the reverse effect. Saturation, on the other hand, only proved to be significant in feeling of sadness. Lower saturation resulted in higher intensity of sadness. On the other hand, hue was only significant on the feeling of calmness. Blue caused greater feelings of calmness as compared to red.
Keywords: product design